Rh(III)-catalyzed [4 + 1]-annulation of azobenzenes with α- carbonyl sulfoxonium ylides toward 3-acyl-(2H)-indazoles. Issue 23 (6th June 2018) - Zhu, Jiawei; Sun, Song; Cheng, Jiang
Graphical abstract: Highlights: Annulation of azobenzenes with α- carbonyl sulfoxonium ylides. Features with excellent yields and good functional group compatibilities. Sulfoxonium ylides served as efficient and stable carbene precursor. Abstract: A Rh(III)-catalyzed [4 + 1]-annulation of azobenzenes with α - carbonyl sulfoxonium ylides was developed to access 2 H -indazoles in moderate to excellent yields with good functional group compatibilities. It proceeded with the sequential insertion of the Rh(III) carbene to the C−H bond and cyclization steps, where sulfoxonium ylides served as efficient and stable carbene precursor.